2013
DOI: 10.4102/ojvr.v80i1.523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mastitis in dairy cows from smallholder farms in Zimbabwe

Abstract: A cross-sectional study was conducted to determine the prevalence of sub-clinical and clinical mastitis and the associated factors in cows from selected smallholder dairy farms in Zimbabwe. Physical examinations were conducted on all lactating cows for evidence of signs of clinical mastitis. Composite milk samples were collected from all lactating cows for bacterial culture and somatic cell counting. Cows were categorised as clinical if they exhibited clinical features of mastitis, or sub-clinical if no appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
21
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
(39 reference statements)
12
21
5
Order By: Relevance
“…Isolation of CNS (10%) is compatible with the results reported in Netherland (10.8%), Sweeden (16%) and Germany (17.17%) (Persson et al, 2011;Schwarz et al, 2010;Sampimon et al, 2009). Although Katsande et al, (2013) and Abrahmsen et al, (2012) reported higher prevalence of CNS (28.7% and 27.6% respectively); these discrepancies may be related to changes in herd management and bacteriological ecology in the herd environment (Pitkala et al, 2004). In this study, the result of isolation of Escherichia coli was almost similar to another study (6.67%) in Bangladesh (Kayesh et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Isolation of CNS (10%) is compatible with the results reported in Netherland (10.8%), Sweeden (16%) and Germany (17.17%) (Persson et al, 2011;Schwarz et al, 2010;Sampimon et al, 2009). Although Katsande et al, (2013) and Abrahmsen et al, (2012) reported higher prevalence of CNS (28.7% and 27.6% respectively); these discrepancies may be related to changes in herd management and bacteriological ecology in the herd environment (Pitkala et al, 2004). In this study, the result of isolation of Escherichia coli was almost similar to another study (6.67%) in Bangladesh (Kayesh et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Another study conducted by Katsande et al, (2013) showed comparatively lower prevalence (16.3%) of SCM in Zimbabwe. Previous studies in different regions of Bangladesh reported that the prevalence of SCM based on California Mastitis Test (CMT) varies from 29% to 37.6% (Islam et al, 2011;Islam et al, 2010) and based on SCC was 55% (Hoque et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…4,24,32,33 By contrast, Klebsiella mastitis outbreaks are only occasionally reported in Europe, 34,35 although a high rate has been reported in a study from the Alps in France (92%). 36 Our low prevalence rates are closely related to the findings in Canada 37 and significantly lower from several other global surveys on the prevalence of Klebsiella intra-mammary infections in Europe, Asia and South America 38-41 which have reported values ranging between 33.5% and 45.0 % and in Africa [42][43][44][45][46][47][48][49] which have reported a prevalence of 15-16%. The absence of Klebsiella spp.…”
Section: Discussionsupporting
confidence: 70%
“…isolates in cases of subclinical mastitis highlights the insignificant role of this enterobacteria in subclinical mastitis contrary to other reports. [42][43][44][45][46]49 The existence of an oro-fecal transmission cycle has been suggested for K. pneumoniae in dairy herds, with fecal shedding resulting in the contamination of feed and water and the subsequent re-ingestion of the organism, resulting in renewed fecal shedding. 15,[50][51][52] Fecal shedding of Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%